The Development of Intelligent Tutoring System in The Military Schools - Kurniawan, Bobi; Meyliana, M.; Warnars, Harco Leslie Hendric Spits; Suharjo, Bambang (Universitas Pendidikan Indonesia (UPI), 2023)
The rapid and fast development of technology affects many aspects of life, especially in the field of education. The application of technology in education is needed to support a more effective and efficient learning process without any space and time constraints. An example is the implementation of the Intelligent Tutoring System (ITS) which is often known as an intelligent learning system. An ITS in the field of military education is needed to produce professional military graduates/HR. Therefore, researchers will examine trends in research development and updates on ITS technology in the military field. Efforts to achieve research objectives are carried out using the Systematic Literature Review method with bibliometric analysis or VOSviewer. The purpose of this study is to become a reference for determining research topics on ITS in the field of education, especially the military.